2020
DOI: 10.3928/01477447-20200624-03
|View full text |Cite
|
Sign up to set email alerts
|

The Early Effect of COVID-19 Restrictions on an Academic Orthopedic Surgery Department

Abstract: The SARS-CoV-2 (COVID-19) pandemic has had a global influence on health care. The authors examined the early effect of hospital- and state-mandated restrictions on an orthopedic surgery department and hypothesized that the volume of ambulatory clinic encounters, office and surgical procedures, and cases would dramatically decrease. A retrospective review was performed of all encounters in an orthopedic surgery department at a level I academic trauma center during a 4-week period, from March 16, 2020, to April … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 3 publications
1
21
0
2
Order By: Relevance
“…5 In orthopedic surgery, non-urgent diagnostic imaging was postponed, outpatient physical therapy and occupational therapy were decreased, and non-urgent elective procedures were postponed. 6,7 As a society, social distancing and travel restrictions have reduced the volume of patients experiencing trauma, while the amount of osteoporotic and fragility hip fractures have remained constant during the pandemic. 5,[8][9][10][11][12][13] There is compelling evidence that early surgery, prompt orthogeriatric care, a multidisciplinary approach, and early postoperative ambulation improves outcomes for patients with hip fractures.…”
Section: Introductionmentioning
confidence: 99%
“…5 In orthopedic surgery, non-urgent diagnostic imaging was postponed, outpatient physical therapy and occupational therapy were decreased, and non-urgent elective procedures were postponed. 6,7 As a society, social distancing and travel restrictions have reduced the volume of patients experiencing trauma, while the amount of osteoporotic and fragility hip fractures have remained constant during the pandemic. 5,[8][9][10][11][12][13] There is compelling evidence that early surgery, prompt orthogeriatric care, a multidisciplinary approach, and early postoperative ambulation improves outcomes for patients with hip fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Fifty-nine articles met the inclusion criteria and were considered for the analysis. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 The excluded thirty-four papers were editorials, letters, duplicate entries, and articles with no discussion on telemedicine even in the full text ( Figure 1 ). The monthly contributions trend of the orthopaedic telemedicine-related articles is shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Most surveys reported widespread adoption of telemedicine as the main patient care modality. 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 Telemedicine can address the general and specialised needs of osteoporotic patients, paediatric deformities, fracture patients, and sports injuries. 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 High patient and doctor satisfaction has been recorded with telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…In many countries, a decrease in elective and non-elective trauma cases was noticed [6] . Earp et al [6] found that surgical cases had decreased by 88%.…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, a decrease in elective and non-elective trauma cases was noticed [6] . Earp et al [6] found that surgical cases had decreased by 88%. Possible reasons for this decline could be due to governmental restrictions or patients choosing to delay (elective) surgeries because of fear of a COVID-19-transmission.…”
Section: Introductionmentioning
confidence: 99%